Pengaruh Pembelajaran Berbasis Proyek Terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Imarida, Imarida (Yayasan Sembilan Pemuda Indonesia, 2024)
Students’ critical thinking skills are still relatively low at SDN 34 Palembang, marked by the low results of the pretest held in this research activity. This indicates that it is necessary to make learning innovations that can encourage students’ critical thinking skills, one of which is project-based learning. This research activity was conducted at SDN 34 Palembang in class VI with science subjects with a total of 30 students. This research activity was carried out to add insight into interactive learning used for students’ critical thinking skills, one of which is project-based learning. Based on the research that has been conducted on the application of project-based learning, it is obtained that students, after receiving this learning, can improve students’ critical thinking skills, marked by higher student posttest results than pretest results, with 86% of students achieving essential skills of thinking indicators.